The Impact of BIM on Design Phase Productivity The West Link Case Study - Al-Khiami, Mohamad Iyad; Zangana, Ali (My University, 2017)
Building information modeling (BIM) or Building information management is a technological and organizational approach with potential benefits to the construction industry. BIM can be divided into several aspects, including scope, visualization, integration and automation. By using BIM, the client, consultants and contractors gains many advantages in aspects of communication, time, cost and the quality of the outcome. In this master thesis, an examination of the productivity gains a project can attain by implementing BIM in the design phase is conducted. The thesis uses a case study approach for this examination, where the “West Link” Project was used as the case. Research was further narrowed down to the “Central Station” Bid-pack. This specific Bid-Pack was chosen as it uses a new procurement strategy that enhances the integration process. The case study has been supported by interviews with the client (Trafikverket) and the contractors (NCC), collecting data from Trafikverket’s database, using the results of surveys conducted by Trafikverket on employees and from direct observations. The master thesis has also developed several KPIs that has been seen to be repeated consistently within the research and are of importance to Trafikverket. These KPIs has been used as an indicator of the current performance of BIM. The Macleamy Time/Effort curve has also been used as a way in assessing the collaboration between stakeholders. The study is of high importance to Trafikverket as it is the first time they implement BIM in such a big scale. It can also be considered important to other clients willing to implement BIM in their organization without prior knowledge of assessing its advantages. The study finds that by using BIM in Trafikerket, paper documents can be reduced, collaboration, information sharing and trust issues can be enhanced. BIM has created closer collaborations between the client and the contractor. The study also shows that there has been an increase in costs and delay in schedule which can be related to the lack of maturity and psychological barriers within the employees of Trafikverket.
Keywords: Samhällsbyggnadsteknik; Civil Engineering